A MEMÓRIA ESQUECIDA DA JUSTIÇA DO TRABALHODE PERNAMBUCO: "O CASO EURICO" (1966) - Marcília Gama Silva (TRF2, 2020)
The article's proposal is based on the study of a traumatic and forgotten memory of the Pernambuco Labor Court, which unfolds from a complaint that involved the crimes of "subversion" and "corruption". This denunciation culminated in the removal of Eurico de Castro Chaves Filho from the post of President of Labor Court, in the years of 1966, whose circumstances were full of implications, only understood through the deepening of the authoritarian imagination that permeated the period. The narrative's path takes place through the work of interconnecting documentary artifacts of different natures. On the onehand, the Administrative Inquiry produced in the Labor Court, which generated another inquiry in the IV Army; and on the other, functional and individual records of the Department of Political and Social Order -DOPS-PE, which helped us to reveal the plotbehind the fact that shook the history of the Regional Labor Court of the Sixth Region, in which it was possible to identify repressive practices constituted in both archival realities referring to the military period.